Peningkatan Kualitas Guru Sekolah Penyelenggara Pendidikan Inklusif dan Terapis di Kota Surakarta - Santi Stanislausia Liem (Jurnal ABDI RAKYAT, 2024)
The Indonesian government has launched inclusive education since 2012, and targets that by 2021 all schools in Indonesia will have implemented inclusive education. However, according to the Ministry of Education and Culture (2019), the number of inclusive schools is only around 11%. The obstacles are the limited number of teachers who are competent, capable of adapting the curriculum, and the lack of adequate learning media. Starting from 2021, NGO CERC from Japan will conduct training on inclusive education, especially regarding autism. The author is involved in training as a material translator, as well as an interpreter in seminars (online and hybrid). The training material includes an introduction to the characteristics of autism, how to overcome problems faced by children, adjustments to teaching methods and learning environments, as well as learning media. This training is very helpful for training participants from inclusive schools, most of whom do not have knowledge about the specifics of autism. The application of teaching methods brings positive results for all stakeholders, both for teaching staff, students, parents of students, as well as non-ABK students. Schools also increasingly have a real picture of the implementation of inclusive education.